A New Burrowing Frog of the Odontophrynus americanus Species Group (Anura, Odontophrynidae) from Subtropical Regions of Argentina, Brazil, and Paraguay - Rosset, Sergio D.; Fadel, Renata Moleiro; Guimaraes, Carla da Silva; Carvalho, Priscila Santos [UNESP]; Ceron, Karoline; Pedrozo, Mariana; Serejo, Renata; Souza, Victoria dos Santos; Baldo, Diego; Mangia, Sarah (Amer Soc Ichthyologists & Herpetologists, 2021)
A new species of frog of the genus Odontophrynus is described from grassland of the subtropical regions of Argentina, Brazil, and Paraguay based on morphological, osteological, bioacoustical, cytogenetic, and molecular evidence. The new species is characterized by having medium size; rostral and eye-nostril glandular warts well developed; several long glandular ridges, longitudinally oriented, on dorsum; several medium-sized, nearly rounded, dark-brown dorsal blotches; light mid-dorsal stripe continuous and well defined or restricted to the head and the urostyle regions; and mid-dorsal stripe, interorbital, and dorsolateral bands with a moderately whitish highlight, light brown, or reddish coloration. Additionally, the new species has a skull with nasals slightly separated both from each other and frontoparietals, and frontoparietal fontanelle not exposed. The advertisement call consists of a single multipulsed note with a dominant frequency of 820-1,121 Hz and a pulse rate of 99.3-140.7 pulses/s. The chromosomal complement is diploid with 2N = 2X = 22 chromosomes and nucleolar organizer regions on the interstitial regions of the short arm of chromosome pair 4. The phylogenetic analysis allowed us to recover the new species belonging to the O. americanus species group with genetic distances from its congeners ranging from 2.11 to 4.82% in a partial sequence of 16S ribosomal RNA gene. The new species is geographically isolated from the other currently known diploid species of the group, but in some localities is found in sympatry or syntopy with the tetraploid O. americanus.